If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + 8 = 5x + 5 Reorder the terms: 8 + 8x = 5x + 5 Reorder the terms: 8 + 8x = 5 + 5x Solving 8 + 8x = 5 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 8 + 8x + -5x = 5 + 5x + -5x Combine like terms: 8x + -5x = 3x 8 + 3x = 5 + 5x + -5x Combine like terms: 5x + -5x = 0 8 + 3x = 5 + 0 8 + 3x = 5 Add '-8' to each side of the equation. 8 + -8 + 3x = 5 + -8 Combine like terms: 8 + -8 = 0 0 + 3x = 5 + -8 3x = 5 + -8 Combine like terms: 5 + -8 = -3 3x = -3 Divide each side by '3'. x = -1 Simplifying x = -1
| 12x+8=90 | | 3+x=3-x | | 9x=15+3x | | 3y+15=4y-20 | | 2x+3(4x+2)=34 | | 28=6g-8 | | 2x-20=x/2+10 | | 48x^3-12x^2-6x=0 | | 54-2x=10x-18 | | 7-(2x-8)=5-3x | | 2x^2=-2x+5 | | 2x=x/2+10 | | 10x+5x-2x=69 | | 208-3x=x+(x+1)+(x+2)+(x+3)+(x+4)-50 | | 3x+36=10x-48 | | y=25x-7 | | x^4+4x^3+1=0 | | 8(m-1)-7(m+3)=-29 | | 3x+108=9x-12 | | -5x-3(-x+1)=7 | | N+6=-44 | | 107-7x=29x+23 | | 2x/4=6*3 | | 150-5x=22x+18 | | -6x-6(-4x-11)=12 | | 12x^2-40=17x | | (x-7)=(x+3) | | y=-4(-2)-5 | | 23=m-9 | | 7.31=d+3.31 | | 5x+2x=55 | | 2-7x=1-6x |